The Effect of Organizational Culture and Work Discipline on Performance - Muh. Ihwan Dwi Putra; Rahmat Kaco; Rohsita Amalyah Rasyid (Newinera Publisher, 2023)
This research investigates the intricate relationship among organizational culture, work discipline, and employee performance within the specific setting of PT Sabrina Jaya Kabupaten Mamuju. By using a multiple linear regression analysis, this study aims to clarify the influence of these factors on the performance of employees. The results of the study indicate that organizational culture has a negligible beneficial impact (β = 0.123) on performance, but work discipline has a large positive effect (β = 0.444). The results of the simultaneous significance test highlight the combined impact of corporate culture and work discipline on employee performance (F = 19.329, p < 0.001). The results of this study highlight the significance of cultivating a supportive organizational culture and using efficient work discipline tactics in order to maximize employee performance. Nevertheless, the lack of a statistically significant correlation between organizational culture and performance necessitates more investigation. This study makes a significant contribution to the comprehension of the intricate dynamics that influence employee performance and provides vital insights for the development of organizational strategies.